PERWILAYAHAN DAN STRATEGI PENGEMBANGAN KOMODITAS KARET (Hevea Brasiliensis) DI INDONESIA - Pasaribu, Andi Pratama; Soetriono, Soetriono (Jurnal Sosial Ekonomi Pertanian, 2009)
Natural rubber is a estate commodity that give the second biggest devisen in Indonesia after palm oil and 85% of its exertion is done by small farmer. This research has aim to analyse production trend of rubber production and also to map base and non base region of rubber production then. It is continued by analysing region economic effect that happened in rubber exertion in the region to regional analysis and for national economic. This research shows that production trend of rubber in Indonesia tends to increase. Beside that, production based region is in Central Kalimantan, South Kalimantan, Jambi, West Kalimantan and South Sumatra. The exertion model is not concentrated in one region but there is none that specialize it self to rubber exertion. Analysis result shows that rubber commodity support plantation activity in Indonesia and also gives added value directly for the base region growth. To optimalize the growth and development needs to conduct development strategy that is integrated.Key words: Production trend, base and non base region